On the Existence of Positive Solutions for a Class of Semilinear Elliptic Systems (Journal of Partial Differential Equations, 1997)
We study the existence of positive solutions for a class of semilinear ellipcic systems in general domains via the blow up argument and degree theory. The main idea can be used to establish the existence of positive solutions for the Navier problems of polyharmonic semilinear equations in general domains.
Keywords: Semilinear elliptic systems; positive solutions; blow up argument; degree theory; polyharmonic semilinear equations